Performance- and value-oriented decision support for supply chain configuration - Marcus Brandenburg; Heinrich Kuhn; Robert Schilling; Stefan Seuring (Logistics Research, 2014)
The task of supply chain (SC) configuration is to establish a product-specific SC for new products. Apart from cross-regional network aspects and inter-disciplinary factors, the problem complexity is driven by dynamics and uncertainties of short product life cycles. SC configuration affects SC performance and value creation. Hence, resulting impacts have to be measured and compared under consideration of dynamics and uncertainties. In the conceptual part of this paper, dynamics and uncertainties of SC configuration are integrated into a conceptual framework for value-based supply chain management. In the modelbased part of this paper, this framework is linked to a discrete-event simulation model. The performance outcomes and value impacts of SC configuration options are empirically assessed in a case study of a fast-moving consumer goods manufacturer. The shortfalls of costfocused decision-making without consideration of capitalrelated factors and non-financial aspects are illustrated.
Keywords: 650; Company value; Discrete-event simulation; Fast-moving consumer goods; New product introduction; Supply chain configuration